1983
DOI: 10.1111/j.1439-0434.1983.tb00549.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary Antimold Activity of Phosethyl AL, A New Brown Rot Fungicide for Citrus Fruits

Abstract: Phosethyl Al (= Aliette) is a new and promising postharvest fungicide against brown rot of citrus fruits. Its effectiveness in controlling green mold (Penicillium digitaum), the major citrus fruit pathogen, was studied on artificially inoculated fruit and compared with that of sodium o‐phenylphenate (SOPP) and thiabendazole (TBZ). In vitro and in vivo experiments have shown that phosethyl Al is capable — although to a lesser extent than SOPP and TBZ — of inhibiting growth of P. digitatum and reducing the inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…In addition, Phytophthora and Pythium spp. were responsible for many pre-and post-harvest problems on fruits and vegetables, including brown rot of citrus (Cohen 1981a, b, 1982, Gutter 1983, and black pod of cocoa (McGregor 1983(McGregor , 1984. Recently, new diseases are emerging caused by these oomycetes; for example, severe rotting and blight of seedlings of soybean (Tomioka et al 2013), root rot disease of legumes (Gaulin et al 2007), etc.…”
Section: Major Diseases Caused By Oomycetesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Phytophthora and Pythium spp. were responsible for many pre-and post-harvest problems on fruits and vegetables, including brown rot of citrus (Cohen 1981a, b, 1982, Gutter 1983, and black pod of cocoa (McGregor 1983(McGregor , 1984. Recently, new diseases are emerging caused by these oomycetes; for example, severe rotting and blight of seedlings of soybean (Tomioka et al 2013), root rot disease of legumes (Gaulin et al 2007), etc.…”
Section: Major Diseases Caused By Oomycetesmentioning
confidence: 99%
“…Root rot on ginseng Sang et al 2006Cohen 1981a, Cohen 1981b, Cohen 1982 Pythium species Damping-off, root-rot Van West et al 2003, Schmitthenner 1985, Cohen 1981a damping-off pathogen" to tomato and cucumber seedlings Balghouthi et al 2013 Root rot disease of legumes Cohen 1981b, Cohen 1982, Gutter 1983, de Cock et al 2008, Balghouthi et al 2012 Souli …”
Section: Disease Caused Referencesmentioning
confidence: 99%
“…Gutter (25) reported that the phosphite-generating compound fosetyl-AI had modest activity on the control of postharvest green mold on orange at concentrations that effectively controlled brown rot. Gutter (25) reported that the phosphite-generating compound fosetyl-AI had modest activity on the control of postharvest green mold on orange at concentrations that effectively controlled brown rot.…”
Section: Controlmentioning
confidence: 99%
“…There are three types of these fungicides commercially available, namely carbamates, acylanilides and alkyl phosphonates (Cohen & Coffey, 1986). A number of experiments using metalaxyl (Farih et al, 1981;Chitzanidis & Lascaris, 1981;Cohen, 1981Cohen, , 1982, and fosetyl-A1 (Gaulliard & Pelossier, 1983;Gutter, 1983;Cohen et al, 1987; have shown good prospects, in recent years, for the control of brown rot of citrus fruits.…”
Section: Introductionmentioning
confidence: 99%